Photoelectrochemical Cells for Artificial Photosynthesis: Alternatives to Water Oxidation. Issue 2 (9th January 2020) - Ru Ng, Andrew Yun; Boruah, Bhanupriya; Chin, Kek Foo; Modak, Jayant M.; Soo, Han Sen
Abstract: Photoelectrochemical cells have been used as one of the most common artificial photosynthetic approaches to mimic natural photosynthetic water splitting reactions. However, despite the tremendous advances made to improve the affordability and efficiency of photoelectrochemical water splitting, it is still not an economically feasible method to produce solar fuels currently since only the H2 evolving reduction half‐reaction generates valuable fuels. Therefore, in this review, we intend to highlight other underexplored substrates and reactions for producing solar fuels in photoelectrochemical cells, as well as alternative architectures including temporally independent and biohybrid systems. We show that besides water oxidation, electrocatalytic or photoredox reactions for pollutant degradation, biomass valorization, and organic chemical synthesis can be or have been successfully adapted for photoelectrochemical cells, thus offering a virtually infinite number of possibilities for artificial photosynthetic applications which generate valuable products in both the reduction and oxidation half reactions. Abstract : Photoelectrochemical cells have historically been employed for water splitting reactions in artificial photosynthesis. In this review, we intend to highlight alternative photoelectrochemical cell capabilities by adapting new photocatalytic and electrocatalytic processes for pollutant degradation, biomass valorization, and chemical synthesis as replacements for water oxidation at the photoanode.